Data‐Driven Design for Metamaterials and Multiscale Systems: A Review - Lee, Doksoo; Chen, Wei (Wayne); Wang, Liwei; Chan, Yu‐Chin; Chen, Wei (Advanced materials (Weinheim), 2024)
Metamaterials are artificial materials designed to exhibit effective material parameters that go beyond those found in nature. Composed of unit cells with rich designability that are assembled into multiscale systems, they hold great promise for realizing next‐generation devices with exceptional, often exotic, functionalities. However, the vast design space and intricate structure–property relationships pose significant challenges in their design. A compelling paradigm that could bring the full potential of metamaterials to fruition is emerging: data‐driven design. This review provides a holistic overview of this rapidly evolving field, emphasizing the general methodology instead of specific domains and deployment contexts. Existing research is organized into data‐driven modules, encompassing data acquisition, machine learning‐based unit cell design, and data‐driven multiscale optimization. The approaches are further categorized within each module based on shared principles, analyze and compare strengths and applicability, explore connections between different modules, and identify open research questions and opportunities. This review highlights the status and opportunities of data‐driven design for metamaterials and multiscale systems, generally built on data acquisition, unit cell design, and multiscale design. Adopting a design‐centered perspective, the primary approaches of each module that represent common threads and overarching principles are categorized, connections across modules are articulated, and open research questions and opportunities are disclosed.